Cervical cancer vaccination awareness and acceptance among the females of Punjab, Pakistan - Minhas, Sadia; Sajjad, Aneequa; Kashif, Muhammad; Rehman, Zobaria; Idrees, Muhammad; Ansari, Farheen (UI Scholars Hub, 2020)
Background: In developing countries like Pakistan, it is essential for health care professionals to have comprehensive knowledge regarding cervical cancer. Methods: A cross-sectional self-administered paper-based questionnaire was administered to patients from 2016 to 2018. This study included 200 females who attended the gynecological OPD of Lady Willingdon Hospital Lahore, Punjab. We evaluated cervical cancer knowledge, screening, prevention, and acceptance towards the vaccination. Data entry and analysis were performed using SPSS version 20. Results: The perception and knowledge related to cervical cancer (28%), screening (3%), prevention (3%), and vaccination (1%) among the females were poor, but a positive attitude was observed towards cervical cancer screening, vaccination, and awareness programs. An extreme lack of knowledge was observed regarding the risk factors associated with cervical cancer and the availability of the cervical cancer vaccine (99%). A significant association (p > 0.005) was noted among the level of education and awareness of cervical cancer, its mode of transmission, and screening tests. Conclusion: The knowledge and perception of cervical cancer and its vaccine among the females of Punjab, Pakistan were inadequate. Efforts should be made to prevent and control cervical cancer in Pakistan by establishing proper strategies, such as health education programs through health care providers and media support.